“Who is Wise to Understand this?” Interpreting Hosea 14:10 through the Lens of the Hermeneutic of Trauma - Poniatowski, Felix (2025)
The epilogue of the Book of Hosea (Hosea 14:10 [Eng. 14:9]) presents a challenge for interpreters. This epilogue implies that the book contains elements that are difficult to comprehend and that only a wise reader can fully grasp its message. This article employs the hermeneutic of trauma as the primary method of analysis. By examining the relationship between Israel and Judah the author concludes that the two kingdoms were in a near-constant state of conflict. This hostility reached its peak during the Syro-Ephraimite War. These strained relations, particularly the Syro-Ephraimite conflict, likely had a profound traumatic effect on the people of Judah, leading them to view their northern neighbors with animosity and even hatred. Regarding the message of the Book of Hosea, it concludes on a hopeful note, promising restoration for Israel. This positive conclusion would likely have been met with rejection and confusion by the people of Judah. In response to this anticipated misunderstanding, the author adds the epilogue, emphasizing that only the wise can understand God’s redemptive love. In conclusion, the application of this analysis to the dating of Hosea 14 is done.
Keywords: historical background of the book of Hosea; Judah; Israel; trauma studies; Syro-Ephraimite war; book of Hosea